2013
DOI: 10.1021/am403595z
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Superoleophilic to Superoleophobic Wetting Control on the Nanostructured Copper Substrates

Abstract: Surfaces with controlled underwater oil wettability would offer great promise in the design and fabrication of novel materials for advanced applications. Herein, we propose a new approach based on self-assembly of mixed thiols (containing both HS(CH2)9CH3 and HS(CH2)11OH) on nanostructured copper substrates for the fabrication of surfaces with controlled underwater oil wettability. By simply changing the concentration of HS(CH2)11OH in the solution, surfaces with controlled oil wettability from the underwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 65 publications
3
67
0
Order By: Relevance
“…In the above XPS analyses, we have demonstrated that the coverage of hydrophobic hydrocarbons at the micro/nanostructured metal surfaces should exceed a critical proportion to behave superhydrophobic, which depends on the surface roughness and the surface composition. That was also confirmed by modifying metal surface with mixed hydrophilic and hydrophobic organics [59]. To recover the superhydrophobic state from the superhydrophilic state after UV-O 3 treatment, the airborne hydrocarbons must replace, insert into and/or cover the already adsorbed superhydrophilic oxygencontaining organics at the surface.…”
Section: Xps Analyses In Uv-o 3 Treatment Of Cu and Au Depositsmentioning
confidence: 84%
“…In the above XPS analyses, we have demonstrated that the coverage of hydrophobic hydrocarbons at the micro/nanostructured metal surfaces should exceed a critical proportion to behave superhydrophobic, which depends on the surface roughness and the surface composition. That was also confirmed by modifying metal surface with mixed hydrophilic and hydrophobic organics [59]. To recover the superhydrophobic state from the superhydrophilic state after UV-O 3 treatment, the airborne hydrocarbons must replace, insert into and/or cover the already adsorbed superhydrophilic oxygencontaining organics at the surface.…”
Section: Xps Analyses In Uv-o 3 Treatment Of Cu and Au Depositsmentioning
confidence: 84%
“…Many experiments have also demonstrated that the microstructure of the Cu(OH) 2 nanowires can be controlled just through varying the immersion time in the solution of NaOH and (NH 4 ) 2 S 2 O 8 . 19,20 After the formation of the nanoneedles structure by a one-step chemical reaction and the subsequent fluoroalkylsilane surface modification, the resultant rough copper mesh shows excellent superhydrophobicity. As shown in Figure 3a, a small water droplet on such mesh can keep a spherical shape with the water CA of 152.8 • ± 1.8 • .…”
Section: Methodsmentioning
confidence: 99%
“…Following this strategy, many mesh and porous materials that are underwater superoleophobic have been fabricated, and these materials have been successfully applied in oil-water separation. [18][19][20][21][22][23][24][25] For example, Jiang and co-workers coated microscale porous stainless steel mesh with a nanostructured hydrogel to give a novel underwater superoleophobic rough mesh. [ 18 ] This hydrogelcoated mesh effi ciently removed water from water-oil mixtures and did not become fouled with oil.…”
Section: Doi: 101002/admi201500650mentioning
confidence: 99%
“…Problems that have not been adequately addressed are the cost of the materials, the equipment required, and the preparation processes required -all of which prevent large-scale applications. Another issue is that the most widely used materials are metal meshes and porous polymers that have rough microscale-nanoscale hierarchical structures, which are generally formed using chemical corrosion or other chemical methods, [20][21][22][23][24][25] meaning that solving one environmental problem (oil pollution) could cause another (disposing of the waste produced to create the superoleophobic material). It is therefore very important that we develop or fi nd stable materials that are underwater superoleophobic and can be used to simply, cheaply, and effi ciently separate large amounts of oil-water mixtures.…”
Section: Doi: 101002/admi201500650mentioning
confidence: 99%
See 1 more Smart Citation